Rhabdomyolysis Caused by Hypothyroidism: Research Progress - Zhou, Qingju; Li, Bin; Tian, Xin (Hormone and Metabolic Research, 2022)
Rhabdomyolysis (RM) refers to the clinical syndrome caused by the release of intracellular substances into the extracellular fluid and blood circulation after rhabdomyocyte destruction due to various etiologies. In severe cases, RM can lead to life-threatening conditions such as acute kidney injury. Hypothyroidism is a rare cause of RM that can lead to missed diagnosis or misdiagnosis, and the condition worsens in the absence of timely and effective treatment. Herein, reported cases of RM caused by hypothyroidism are summarized, and clinical diagnosis and treatment recommendations are proposed to facilitate early identification and treatment of the disease.
Keywords: hypothyroidism; thyroid; rhabdomyolysis; creatine kinase; acute kidney injury